A Survey on One Health Perception and Experiences in Europe and Neighboring Areas - Chiesa, Francesco; Tomassone, Laura; Savic, Sara; Bellato, Alessandro; Mihalca, Andrei Daniel; Modry, David; Häsler, Barbara; De Meneghi, Daniele (Frontiers in Public Health, 2021)
A questionnaire survey was promoted under the COST Actions “Network for Evaluation of One Health-NEOH” and “European Network for Neglected Vectors and Vector-Borne Infections-EURNEGVEC”, from June 2016 to April 2017, to collect information on the existence of One Health (OH) collaboration and implementation of OH initiatives in 37 EU COST Countries. The questionnaire was to be answered by key respondents representing the three major OH components: (i). Animal Health; (ii). Human Health/Public Health; (iii). Environmental Health. A target respondent rate of nine respondents/country was aimed for, representing the following categories: (i). ministries; (ii). academia-research; (iii). private sector and NGOs, associations and scientific societies. The questionnaire, composed of 27 questions organized in six sections, was circulated to target respondents by Committee Members of the two COST actions. A total of 171 respondents from 34 countries completed the questionnaire, mainly belonging to academic and research institutions (55.5%), and to Animal Health/Animal Science fields (53.8%). Although the majority (57.9%) declared they had heard about OH, few respondents (10.7%) provided a complete definition. The “human” and “animal” elements prevailed over other key elements of OH definition (ecosystem, intersectoral, transdisciplinary, holistic, collaboration). Overall, 62.6% respondents declared to take part in OH initiatives. Antimicrobial resistance, avian influenza and environmental pollution were cited as the top three OH issues over the past 5 years. Limitations and gaps in intersectoral collaboration included communication and organizational problems resulting in poor networking, differing priorities and a lack of understanding between sectors. Regarding control and monitoring of zoonotic diseases, respondents from different sectors preferentially selected their own directorates/ministries while actually in most countries both Ministry of Health and Ministry of Agriculture are engaged. According to respondents, the level of awareness of OH amongst the general public is limited. Similarly, a dearth of opportunities of collaborations at different institutional and/or professional levels was described. Our survey provided an overview of how respondents in COST countries perceived and experienced OH and current limits to OH implementation. Identifying how initiatives are currently working and knowing the promoting and hindering factors allowed suggesting strategies to promote efficiency and effectiveness of OH implementation in the future.